2013
DOI: 10.1155/2013/629469
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness and Epilepsy: A Systematic Review

Abstract: Background. Sleep complaints are common in patients with epilepsy (PWE). Excessive daytime sleepiness (EDS) is one of the most reported complaints and its impact is still a matter of debate. Objective. Evaluate the relationship between EDS and epilepsy, with emphasis on prevalence, assessment, and causes. Methods. A systematic review on PubMed database in the last 10 years (2002 to 2012). The search returned 53 articles and 34 were considered relevant. After citation analysis, 3 more articles were included. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…Also, sleep deprivation is generally considered to trigger or worsen seizures in patients with epilepsy [ 4 , 5 ]. On the other hand, seizures often influence the quality and quantity of sleep, causing irregular sleep patterns or circadian disruption in epileptic patients [ 6 , 7 ]. Furthermore, antiepileptic drugs commonly affect sleep [ 8 ], making the interactions between sleep and seizures even more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Also, sleep deprivation is generally considered to trigger or worsen seizures in patients with epilepsy [ 4 , 5 ]. On the other hand, seizures often influence the quality and quantity of sleep, causing irregular sleep patterns or circadian disruption in epileptic patients [ 6 , 7 ]. Furthermore, antiepileptic drugs commonly affect sleep [ 8 ], making the interactions between sleep and seizures even more complex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dopaminergic rescue of Rogdi mutant sleep revealed a novel sleep-regulatory mechanism that functionally links a specific subset of sleep-promoting GABAergic neurons to a wake-promoting dopaminergic pathway. Since epilepsy, a well penetrated phenotype in KTS patients, implicates GABAergic transmission 10 12 and sleep disorders 13 16 , our findings provide an important genetic clue to understanding the molecular and neural pathogenesis of KTS.…”
Section: Introductionmentioning
confidence: 78%
“…GABA has long been implicated in many aspects of neural dysfunction including seizures 10 12 , a well-penetrated neurological phenotype in KTS patients. Moreover, sleep deficits frequently accompany epilepsy 13 16 , and their severity is positively correlated in human epileptic patients and animal models 44 46 . In fact, sleep deprivation can cause or even aggravate epileptic seizures 46 48 .…”
Section: Resultsmentioning
confidence: 99%
“…We found an EDS prevalence of 25.2% in the patient group, and found no differences between the patient and control groups. In a recent literature review, 23 the prevalence of EDS in epilepsy was found to vary from 10 to 48%. In general, this prevalence was higher than 11.6% in the general population.…”
Section: Discussionmentioning
confidence: 99%